An innovative lightweight gravity installed plate anchor and its keying properties in clay. (January 2020) - Tong, Yuming; Han, Congcong; Liu, Jun
Highlights: An innovative lightweight gravity installed plate anchor (L-GIPLA) is put forward. Two anchor types, triangular and peltate (shield) L-GIPLAs, are proposed and the anchor keying properties are also investigated. Parametric analyses are carried out to study the performance of the L-GIPLAs. Abstract: This study puts forward an innovative lightweight gravity installed plate anchor (L-GIPLA). The L-GIPLA is dynamically installed with the aid of a booster, which is connected at the anchor tail during installation and is retrieved for re-use after installation. The L-GIPLA is designed with the aim of reducing the installed expense, increasing the anchor embedment depth and hence the anchor capacity, and expanding the usage in various seabed sediments. Moreover, the anchor can dive deeper into the soil and obtain higher capacity when the uplift load is beyond the anchor initial capacity, hence the anchor is not vulnerable to be pulled out of the seabed under extreme conditions. Compared with other anchor types, the present L-GIPLA has low fabrication cost and high efficiency in capacity. Two anchor types, triangular and peltate (shield) L-GIPLAs, were proposed in this study and the keying properties of the anchors were investigated using plasticity analysis. Parametric analyses were then carried out to study the effects of padeye offset, padeye eccentricity and loading angle on the anchor trajectory and capacity mobilization. The difference between the two anchors in anchor embedment loss, ultimate embedment depth and capacity were also systematically presented. The optimized padeye offset angles and loading angles at the mudline were also recommended.